The self in Kierkegaard's pseudonyms - Elrod, John W. (International journal for philosophy of religion, 1973)
This is essentially what I take to be Kierkegaard's ontological foundation of human existence. It is the structure which both makes possible and unifies the different modes of existing which he so fully describes in his pseudonyms. The further task is one of demonstrating concretely the relation of these modes (stages) of existing to his ontology.